Effervescence-assisted liquid phase microextraction prior to slotted quartz tube-flame atomic absorption spectrometry for cadmium determination in domestic wastewater samples - Borahan, Tulay; Karlidag, Nazime Ebrar; Yagci, Ozlem; Bakirdere, Sezgin (SPRINGER INT PUBL AG, 2021)
This paper describes an effervescence-assisted liquid phase microextraction (EA-LPME) method coupled to the SQT-FAAS system for determining trace levels of cadmium in domestic wastewater samples. Preconcentration of the cadmium ions was carried out by forming carbon dioxide bubbles with the help of effervescent tablets without the need for a dispersive solvent. 1-undecanol was used both as the extractant and solidifying agent for the tablets, and the complexation of the Cd metal was provided by diphenylcarbazone. To achieve maximum efficiency in the extraction process, optimization steps were investigated individually and optimized. Under the optimum conditions, LOD and LOQ values calculated for the developed method were 0.38 and 1.3 mu g/L, respectively. An 84-fold enhancement in the detection power of the FAAS system was achieved with the proposed method. Developed EA-LPME-SQT-FAAS method was applied to domestic wastewater samples and the recovery results demonstrated high experimental precision (%RSD < 10) with percent recoveries close to 100%. Developed method is easy, sensitive and accurate for the determination of analyte.
Keywords: Cadmium; Effervescent tablet; Slotted quartz tube-flame atomic absorption spectrophotometry; FLOATING ORGANIC DROP; DEEP EUTECTIC SOLVENT; FAAS DETERMINATION; FATTY-ACID; PRECONCENTRATION; COBALT; LEAD; FUNGICIDES; COPPER; BASE; Chemistry